Actor fluidity and knowledge persistence in regional inventor networks - Michael Fritsch; Moritz Zöllner (Economies, 2022)
The development of inventor networks is characterized by the addition of a significant number of new inventors, while a considerable number of incumbent inventors discontinue. We estimated the persistence of knowledge in the inventor networks of nine German regions using alternative assumptions about knowledge transfer. Based on these estimates, we analyzed how the size and structure of a network may influence knowledge persistence over time. In a final step, we assessed how persistent knowledge as well as the knowledge of new inventors affect the performance of regional innovation systems (RIS). The results suggest that the knowledge of new inventors is much more important for RIS performance than old knowledge that persists.
Keywords: O3; R1; D2; D8; 330; innovation networks; knowledge; patents; persistence; R&D cooperation